IMPLEMENTASI APLIKASI KUMPULAN HADIS BERBASIS ANDROID PADA TPA AL-FATAH KOTA PRABUMULIH - Yeni Yuliana (IAIN Bengkulu, 2022)
Al-Fatah TPA Prabumulih city is located on Jl. Lekipali Prabumulih east of Prabumulih city, South Sumatra. TPA Al-Fatah Prabumulih City conducts teaching and learning activities like schools in general. Where the teacher still uses a system that is still fairly simple, manual (conventional) by using books that are considered less interactive, especially in teaching the hadiths of Rassullah SAW. This study aims to implement an android-based hadith collection application for early childhood in the learning process located at the Al-Fatah TPA Prabumulih City. In this application there is teaching about daily hadith materials such as hadith about the obligation to study, hadith about prayer, hadith about fasting and intentions etc.The research approach uses a qualitative approach. There is also data obtained by using interview observations and documentation. After the data is collected using the percentage formula, then compiled, explained by the process and meaning (subject perspective) is more highlighted in this study. While the theoretical basis is more used as a guide so that the research focus is in accordance with the facts on the ground.While the data analysis used was: recording the things found in the field, collecting and categorizing data, concluding data from data analysis and then getting the results from the research, namely: Implementation of the Android-Based Hadith Collection Application at the Al-Fatah TPA Prabumulih city including: The first is the implementation of the Adobe Flash CS6 application for hadith material and the second is by using the Adobe Flash CS6 application using the Android-based MDLC method, children can learn about hadith more fun and easily memorize them in everyday life.